Comparative moral economies of crisis. (June 2022) - Manning, Benjamin; Browne, Craig
At times of crisis, existing institutional arrangements of societies are thrown into question. Crises that occur in multiple societies simultaneously present rare opportunities for comparative empirical analysis. Social theory can reveal the framing conditions of the responses to crises and the sources of variations between them. This paper compares the immediate responses of the Australian, UK and US governments to the global COVID-19 pandemic, particularly with regard to financing lockdowns, and points out significant differences between the three approaches. Drawing on Polanyi's method of institutional analysis, we compare the responses of these same national groups to an earlier crisis, the Japanese prisoner of war camps during the Second World War, to show similar patterns of integration recurring eight decades apart. This analysis shows that aspects of moral economies that are not usually apparent can become pronounced during crises, and points to the importance of enduring social imaginaries.